FAKTOR-FAKTOR YANG MEMPENGARUHI KUNJUNGAN WISATAWAN KE KOTA SABANG. - Mawardi, Mohd Nur Syechalad, Sofyan Syahnur. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: This study aims to determine the effect of inflation and per capita income of the domestic tourist visits to the city of Sabang and to determine the effect of exchange rate and the annual tourism on tourist arrivals to Sabang city. The method used is a quantitative method of analysis methods and tools include: Multiple Linear Regression. The data used in the form of secondary data obtained from the Central Bureau of Statistics of Sabang city, Bank Indonesia and Regional Development Planning Board and Department of Culture and Tourism of Sabang city. The results of the data analysis showed that per capita income has a positive effect on the number of domestic tourists to Sabang city and statistically significant. While inflation variables negatively affect the number of domestic tourist visits to of Sabang city, was not statistically significant . And for analysis of the data on the number of foreign tourists to Sabang city showed that negative exchange rate effect and the amount of the annual event has a positive effect on the number of foreign tourists to Sabang city. Exchange rate variable was not statistically significant, while the annual number of variables showed statistically significant. While inflation variables negatively affect the number of domestic tourist visits to Sabang city, was not statistically significant. And for analysis of the data on the number of foreign tourists to Sabang city showed that negative exchange rate effect and the amount of the annual event has a positive effect on the number of foreign tourists to Sabang city. Exchange rate variable was not statistically significant, while the annual number of variables showed statistically significant. Sabang city should take advantage of the potential to be excellent in the area happens to be more specialized in order to strengthen the economy of the city of Sabang. For local governments should be able to take advantage of Sabang potential to be excellent in the area in order to improve the welfare of the people of Sabang. From the results of this study are expected also to be used as economic indicators beginning to Sabang City Government to conduct economic surveys that can provide a comprehensive overview of Sabang City Government. As well as for further research to be able to add new research models that can forward the complete picture. Keywords: tourists, inflation, per capita income, the exchange rate, the annual event. Abstrak: Penelitian ini bertujuan mengetahui pengaruh Inflasi dan pendapatan perkapita terhadap kunjungan wisatawan nusantara ke Kota Sabang dan untuk mengetahui pengaruh nilai kurs dan acara tahunan pariwisata terhadap kunjungan wisatawan mancanegara ke Kota Sabang. Metode yang digunakan adalah metode kuantitatif dengan metode dan alat analisis antara lain: Regresi Linier Berganda. Data yang digunakan dalam bentuk data sekunder yang di dapat dari BPS Kota Sabang, Bank Indonesia dan Bappeda Kota Sabang. Hasil analisis data menunjukkan bahwa pendapatan perkapita berpengaruh positif terhadap jumlah wisatawan nusantara ke Kota Sabang dan secara statistik signifikan. Sedangkan variabel inflasi berpengaruh negatif terhadap jumlah kunjungan wisatawan nusantara ke Kota Sabang, secara statistik tidak signifikan. Dan untuk analisis data terhadap jumlah wisatawan mancanegara ke Kota Sabang menunjukkan bahwa tingkat kurs berpengaruh negatif dan jumlah acara tahunan berpengaruh positif terhadap jumlah wisatawan mancanegara ke Kota Sabang. Secara statistik variabel kurs tidak signifikan, sedangkan variabel jumlah acara tahunan secara statistik menunjukkan signifikan. Kota Sabang harus memanfaatkan potensi yang menjadi primadona di daerah tersebut agar terjadi menjadi lebih terspesialisasi untuk memperkuat perekonomian Kota Sabang. Untuk pemerintah daerah kota Sabang harus mampu memanfaatkan potensi yang menjadi primadona di daerah tersebut agar dapat meningkatkan kesejahteraan masyarakat Kota Sabang. Dari hasil penelitian ini diharapkan juga agar dapat dijadikan indikator ekonomi awal bagi Pemerintah Daerah Kota Sabang untuk melakukan survei ekonomi yang dapat memberikan gambaran komprehensif bagi Pemko Sabang. Serta bagi peneliti selanjutnya untuk dapat menambahkan model-model penelitian terbaru sehingga ke depan di dapat gambaran yang lengkap. Kata kunci: Wisatawan, inflasi, pendapatan perkapita, kurs, acara tahunan.